Spread of blaCTX-M-9 and Other Clinically Relevant Resistance Genes, Such as mcr-9 and qnrA1, Driven by IncHI2-ST1 Plasmids in Clinical Isolates of Monophasic Salmonella enterica Serovar Typhimurium ST34 - Xenia Vázquez; Javier Fernández; Miriam Alkorta; María de Toro; M. Rosario Rodicio; Rosaura Rodicio (MDPI AG, 2023)
The monophasic 4,[5],12:i:-variant of Salmonella enterica serovar Typhimurium with sequence type ST34 has become one of the most prevalent non-typhoidal salmonellae worldwide. In the present study, we thoroughly characterized seven isolates of this variant detected in a Spanish hospital and selected based on cefotaxime resistance and cefoxitin susceptibility, mediated by blaCTX-M-9. For this, conventional microbiological techniques, together with whole genome sequencing performed with the Illumina platform, were applied. All selected isolates carried the resistance region RR or variants therein, and most also contained the SGI-4 genomic island. These chromosomal elements, typically associated with monophasic S. Typhimurium ST34, confer resistance to traditional antibiotics (ampicillin, streptomycin, sulfonamides, and tetracycline) and tolerance to heavy metals (mercury, silver, and copper). In addition, each isolate carried a large IncHI2-ST1 conjugative plasmid containing additional or redundant resistance genes. All harbored the blaCTX-M-9 gene responsible for cefotaxime resistance, whereas the qnrA1 gene mediating fluoroquinolone resistance was detected in two of the plasmids. These genes were embedded in ISCR1-bearing complex class 1 integrons, specifically In60-like and In36-like. The mcr-9 gene was present in all but one of the IncHI2-ST1 plasmids found in the analyzed isolates, which were nevertheless susceptible to colistin. Most of the resistance genes of plasmid origin clustered within a highly complex and variable region. The observed diversity results in a wide range of resistance phenotypes, enabling bacterial adaptation to selective pressure posed by the use of antimicrobials.